2015
DOI: 10.1179/1743132815y.0000000034
|View full text |Cite
|
Sign up to set email alerts
|

Music-supported therapy (MST) in improving post-stroke patients' upper-limb motor function: a randomised controlled pilot study

Abstract: This study supports that MST, when combined with conventional treatment, is effective for the recovery of motor skills in post-stroke patients. Additionally, it suggests that apart from the repetitive practices of MST, music may play a unique role in improving upper-limb motor function for post-stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 41 publications
1
43
1
2
Order By: Relevance
“…In total, 10 eligible studies (13 analyses, 358 participants)14151617181920212223 were identified and incorporated into the systematic review and meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 10 eligible studies (13 analyses, 358 participants)14151617181920212223 were identified and incorporated into the systematic review and meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies1518 presented the Fugl-Meyer assessment score (FMA), the Wolf Motor Function Test score (WMFT) and the Wolf Motor Function Test time, with no heterogeneity found in any of the 3 evaluated measures ( P  > 0.05, I 2  < 10%). The results of the FMA (SMD = 0.09, 95% CI: −0.36~0.54), the WMFT score (SMD = 0.30, 95% CI: −0.15~0.74) and the WMFT time (SMD = 0.30, 95% CI: −0.15~0.74) revealed that music-supported therapy group achieved better curative effects than the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, music‐supported therapy (MST) aims to enhance the motor deficits of the upper extremity through the training with musical instruments and provides real‐time auditory feedback about the performance, which serves as a basis for motor learning . Studies in the subacute and chronic stage of the rehabilitation process have demonstrated that stroke patients boost their motor function after the MST training . A 4‐week program of MST can improve dexterity, smoothness, and velocity of movements and induce intrahemispheric functional reorganization within the lesioned hemisphere .…”
Section: Introductionmentioning
confidence: 99%
“…the rehabilitation of mobility while listening to music, is effective in the improvement of gait and other activities which depend on the ability to walk; however, interestingly, its role in the assessment of quality of life has not been shown (de Dreu, van der Wilk, Poppe, Kwakkel, & van Wegen, 2012). The effects of MT are also used in the rehabilitation of upper limbs (Tong et al, 2015) and appropriately selected music training is used in cognitive impairments (Baker & Tamplin, 2006;Bukowska, 2012).…”
Section: Music Therapy and Quality Of Lifementioning
confidence: 99%